The Complex Governance and Public Engagement Challenge of the AD|ARC Project: Research to Support Farming Communities Across the UK - Madden, Laura; Loftus, Rachael; Morrison-Rees, Sian; Lowe, Sarah; Pryce, Freya; Caskie, Paul (International Journal of Population Data Science, 2025)
Objectives Administrative Data | Agricultural Research Collection is a complex research project involving four nations, a mixture of business-level, household-level and person-level data, and diverse stakeholders. The engagement and communications workstream aims to build trust, inform the programme of work, support and enhance research, and deliver findings that meet stakeholders’ expectations. Methods The project deployed a bespoke engagement and communications framework to meet these objectives. This presentation shares key elements of AD|ARC project's engagement and communications framework and strategy: Multi-region Approach: Balancing the need for a harmonised, federated resource while respecting regional differences in data, trusted research environments, and stakeholder perspectives. Transparency and Trust: Engaging diverse stakeholders, including farmers, researchers, and policymakers, to build trust, support and legitimacy. Collaborative Decision-Making: Interacting with diverse partners, (data owners, researchers, research subject representatives) to refine research questions. Outreach and Dissemination: A multi-method, iterative approach to raise awareness, share and promote the project. Results The selection of AD|ARC as an ADR UK Flagship Dataset demonstrates the project’s success across all aspects of the engagement and communications framework and strategy. The iterative approach led to ADR UK funding two fellows to utilise the England and Wales Research-Ready Datasets, with a comprehensive plan from each fellow that will provide actionable evidence to inform policymaking. The strategy is fundamental to data acquisition choices, with the project integrating diverse perspectives into the creation of comparable Research-Ready Datasets. Engaging and collaborating with diverse stakeholders supports the established research programme. Opportunities to reflect throughout the lifespan of the project continue to result in useful learning which is incorporated into future strategy. Conclusion The presentation will reflect on challenges faced and lessons learned during the lifespan of the project. It will draw out implications for research and public engagement that could apply to any complex research project.